Sphingosine-1-Phosphate: A Potential Biomarker and Therapeutic Target for Endothelial Dysfunction and Sepsis?. Issue 6 (June 2017) - Winkler, Martin S.; Nierhaus, Axel; Poppe, Annika; Greiwe, Gillis; Gräler, Markus H.; Daum, Guenter
Abstract : ABSTRACT: Sepsis is an acute life-threatening multiple organ failure caused by a dysregulated host response to infection. Endothelial dysfunction, particularly barrier disruption leading to increased vascular permeability, edema, and insufficient tissue oxygenation, is critical to sepsis pathogenesis. Sphingosine-1-phosphate (S1P) is a signaling lipid that regulates important pathophysiological processes including vascular endothelial cell permeability, inflammation, and coagulation. It is present at high concentrations in blood and lymph and at very low concentrations in tissues due to the activity of the S1P-degrading enzyme S1P-lyase in tissue cells. Recently, four preclinical observational studies determined S1P levels in serum or plasma of sepsis patients, and all found reduced S1P levels associated with the disease. Based on these findings, this review summarizes S1P-regulated processes pertaining to endothelial functions, discusses the possible use of S1P as a marker and possibilities how to manipulate S1P levels and S1P receptor activation to restore endothelial integrity, dampens the inflammatory host response, and improves organ function in sepsis.